Genetic Testing for Rare Diseases: A Systematic Review of Ethical Aspects - Kruse, Judith; Mueller, Regina; Aghdassi, Ali A.; Lerch, Markus M.; Salloch, Sabine (Frontiers in Genetics, 2022)
Genetic testing is associated with many ethical challenges on the individual, organizational and macro level of health care systems. The provision of genetic testing for rare diseases in particular requires a full understanding of the complexity and multiplicity of related ethical aspects. This systematic review presents a comprehensive and detailed overview of all ethical aspects relevant to genetic testing for rare diseases as discussed in the literature. The electronic databases Pubmed, Science Direct and Web of Science were searched, resulting in 55 relevant publications. From the latter, a total of 93 different ethical aspects were identified. These ethical aspects were structured into three main categories (process of testing, consequences of the test outcome and contextual challenges) and 20 subcategories highlighting the diversity and complexity of ethical aspects relevant to genetic testing for rare diseases. This review can serve as a starting point for the further in-depth investigation of particular ethical issues, the education of healthcare professionals regarding this matter and for informing international policy development on genetic testing for rare diseases.